Filipino textiles conservation and preservation. - Elvena, Evelyn
Evelyn Elvena, textile conservator of the National Museum of the Philippines, reports on the characteristics of Filipino textiles, weaving patterns, conservation and preservation techniques, status of ethno-archaeology and future plans of the museum for collections...
Keywords: Preservation; Conservation; Textiles